Wound Healing Effects of Litsea garciae Extracts: In vitro Study on Fibroblast Cells - Zinyin, Ling (Universiti Malaysia Sarawak, 2024)
Wound healing is a complex physiological process that involves regeneration of new cells and substitution of damaged cells after the onset of lesion. Wound healing involves the collaboration of many cell types and categorised into four overlapping main phases: haemostasis, inflammation, proliferation and remodelling. Although various wound healing treatments are currently available, the long-term usage of the medications has caused some adverse effects. To date, many traditional medicinal plants have been studied and widely used for various diseases due to their high efficacy, safety, and low cost. Litsea garciae (L. garciae) has many traditional medicinal uses and has been used by the indigenous people of Borneo Island to treat various diseases. However, its wound healing potential in skin wound therapy has not yet been investigated. Therefore, this study aimed to investigate whether the lipid and methanolic extracts of Litsea garciae could facilitate the process of in vitro wound healing and has a beneficial effect on the proliferation and migration of fibroblasts during in vitro wound healing. Total lipids were extracted using two different solvents: petroleum ether (PE) and Bligh and Dyer (BD). In addition, the crude methanolic extracts were prepared using 80% methanol. Firstly, the fatty acids composition of the lipid pulp and seed extracts of L. garciae were analysed using gas chromatography-mass spectrometry (GC-MS). The antimicrobial activities of the L. garciae lipid and methanolic pulp and seed extracts were evaluated through disk diffusion and broth microdilution assays. For the investigation of the potential wound healing properties of the L. garciae extracts, an in vitro study on the migration and chemotactic motility of the human dermal fibroblasts were conducted using wound scratch assay and transwell assay respectively. The effects of L. garciae extracts on the stimulation of the collagen type I, epidermal growth factor (EGF) and vascular endothelial growth factor (VEGF) expression levels were evaluated using enzyme-linked immunosorbent assays (ELISA). This study showed that the prominent fatty acids in the L. garciae lipid seed extracts were lauric acid, palmitic acid, oleic acid, and linoleic acid. While for the L. garciae lipid pulp extracts, the predominant fatty acids were palmitic acid, stearic acid, oleic acid, and linoleic acid. All the L. garciae extracts exhibited mild antibacterial activities against the Gram-positive bacteria while Gram-negative bacteria exerted a weaker susceptibility towards the L. garciae extracts. The lipid pulp extracts were found to exhibit a stronger antimicrobial activity than the methanolic pulp extract while methanolic seed extract showed higher inhibition effect as compared to the lipid seed extracts. As for the wound healing property investigations, there were enhancement in the migration and chemotactic motility of fibroblasts treated with all the L. garciae pulp and seed extracts, but not with the methanolic seed extract. The expression levels of the collagen type I, EGF and VEGF by the wounded fibroblasts were ameliorated in the presence of the L. garciae extracts. These findings validated the ability of L. garciae extracts in promoting the wound healing process, which might be attributed to the presence of phytochemicals and fatty acids in the extracts. This study suggested that the L. garciae pulp and seed extracts might be a potent medication for skin wound healing.